Development of Learning Achievement in English for Marketing Subject by Using Project Work “B.E. Hometown Products Fair" - et. al., Khacheenuj Chaovanapricha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were (1) to study the learning achievement of the second year Business English students, the Faculty of Humanities and Social Sciences, Suan Dusit University in English for Marketing subject after using project work “B.E. Hometown Products Fair” to have an average score at 70% or more, and (2) to study the students’ satisfaction toward the learning through project work “B.E. Hometown Products Fair” in English for Marketing subject. Quantitative research was used and research instruments were (1) the progress test and (2) the satisfaction questionnaire. Data collected from the sampling group who was 76 second year Business English students, the Faculty of Humanities and Social Sciences, Suan Dusit University. The statistics used for data analysis were frequency, means, and the Standard Deviation (S.D.). The findings revealed that the average scores of the students in English for Marketing subject were 73.25% and the students’ satisfaction of learning through project work was 87.98%.